2001
DOI: 10.1590/s1519-566x2001000400014
|View full text |Cite
|
Sign up to set email alerts
|

Host Deprivation Effect on Reproduction and Survival of Wolbachia-Infected and Uninfected Trichogramma kaykai Pinto & Stouthamer (Hymenoptera: Trichogrammatidae)

Abstract: -The effect of temporary host deprivation on the reproduction and survival of Trichogramma kaykai Pinto & Stouthamer was determined by comparing a Wolbachia-infected (thelytokous) and an arrhenotokous line of T. kaykai when reared on Trichoplusia ni Hübner (Lepidoptera: Noctuidae) eggs. The progeny produced by both arrhenotokous and thelytokous females decreased with increasing periods of host deprivation, but arrhenotokous females produced significantly more progeny than thelytokous females regardless of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
3
10
0
1
Order By: Relevance
“…All lines used in this study produced highly female-biased offspring sex ratios as virgins, producing some males as they aged. This is a pattern typical of Wolbachia infected T. kaykai females (Hohmann et al 2001;Miura & Tagami 2004). Consistent with this parthenogenesis, the lines also tested positive for Wolbachia infection, based on 16S rDNA.…”
Section: Wolbachia Infection Statussupporting
confidence: 75%
“…All lines used in this study produced highly female-biased offspring sex ratios as virgins, producing some males as they aged. This is a pattern typical of Wolbachia infected T. kaykai females (Hohmann et al 2001;Miura & Tagami 2004). Consistent with this parthenogenesis, the lines also tested positive for Wolbachia infection, based on 16S rDNA.…”
Section: Wolbachia Infection Statussupporting
confidence: 75%
“…Some studies have reported parasitism rates, emergence, and progeny production to be low in thelytokous organisms when compared with their arrhenotokous counterparts (Miura and Tagami 2004;Hohmann et al 2001). However, other characteristics, such as mature ovarian eggs at emergence, can be similar (Miura and Tagami 2004) and thelytokous wasps may have relatively greater longevity and higher intrinsic rates of natural increase (Miura and Tagami 2004), as well as more rapid responses to hosts (Silva et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these traits are morphological or physiological, such as fecundity, longevity, adult size, and parasitism rates (Grenier and De Clercq 2003). Reductions in parasitism rates, emergence, progeny production, and survivorship of Wolbachia-infected Trichogramma kaykai Pinto and Stouthamer (Hymenoptera: Trichogrammatidae) have been reported (Miura and Tagami 2004;Hohmann et al 2001). On the other hand, other parameters such as numbers of mature ovarian eggs at emergence of T. kaykai (Miura and Tagami 2004) are similar in infected and uninfected strains.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their similar adult life span, thelytokous parasitoids produced signiÞcantly fewer offspring than arrhenotokous ones (Wang and Smith 1996). In Trichogramma kaykai Pinto & Stouthamer reared on Trichoplusia ni (Hü bner) (Lepidoptera: Noctuidae) eggs, arrhenotokous wasps produced more progeny and lived longer than their thelytokous counterparts (Hohmann et al 2001). When reared on Apodemia mormo (C. Felder & R. Felder) (Lepidoptera: Riodinidae) eggs, thelytokous Tr.…”
Section: Discussionmentioning
confidence: 99%